Optimalisasi Target dan Realisasi Pajak Pada E-Filling di Kota Bandung - Sri Astuti Wulandani; Tria Amallia; Zafira Nur Yusra (Department of Public Administration, 2022)
One form of tax administration modernization for the use of information technology in the taxation sector is the use of E-Filling. In general, the E-Filling system is still less attractive to taxpayers. It can be seen that there are still very few E-Filling users in Indonesia. This study aims to determine the target optimization and realization of e-filling taxes in the city of Bandung. Researchers find information using optimization indicators that are guided by three aspects, namely goals, decision alternatives, and limited resources. This research method uses descriptive research using a qualitative approach and the source of data used in this study is primary data which is the result of interviews. The data analysis technique used is in the form of data reduction, data presentation, and drawing conclusions. The results of the research based on optimization indicators, the use of E-Filing by Bandung City Taxpayers has been implemented well.Keywords: Target, Tax, E-Filling